TRENDS IN LOGISTICS BENCHMARKING: A REVIEW OF THE INTERNATIONAL LITERATURE - Milnitz, Diego; Luna, Monica Maria Mendes (Editora Impacto Científico, 2025)
Globalization and the intensification of competition have placed logistics at the core of organizational strategies, being considered the “last frontier” for competitiveness gains. In this context, benchmarking emerges as an essential tool to evaluate logistics performance, identify best practices, and support continuous improvement processes. This article aims to review the international literature on benchmarking applied to logistics, building a bibliographic portfolio of the most relevant publications and analyzing their main contributions. Methodologically, a structured literature review was conducted in the Scopus and Web of Science databases, followed by bibliometric analysis supported by the model proposed by Marasco (2008). The resulting portfolio included 11 main articles and 39 supporting references, allowing the identification of recurring authors, journals, and keywords. The findings indicate that research is concentrated between 2006 and 2009, highlighting journals such as Benchmarking: An International Journal and Supply Chain Management: An International Journal. The most recurrent themes involve logistics benchmarking, strategic management, data analysis, logistics services, and, more recently, sustainability and reverse logistics. The most frequently cited authors were Hokey Min, Seong Jong Joo, Jukka Korpela, and Markku Tuominen, evidencing the concentration of research in North America and Europe. As a contribution, the study synthesizes the state of the art on logistics benchmarking, points out gaps such as the low presence of studies in Brazil, and suggests future research agendas focused on digitalization, green logistics, integration in global supply chains, and performance measurement in collaborative environments.DOI: https://doi.org/10.56238/edimpacto2025.069-005